2021
DOI: 10.1093/heapro/daab077
|View full text |Cite
|
Sign up to set email alerts
|

Expert by Experience engagement in gambling reform: qualitative study of gamblers in the United Kingdom

Abstract: Summary To explore how Experts by Experience (EbyE) conceptualize key priorities for preventing and reducing gambling-related harm in the United Kingdom (UK). To identify barriers and facilitators to EbyE engagement in decisions for gambling research, education, treatment (RET) and policy development. Qualitative study utilizing semi-structured interviews with 20 participants from the UK between March and July 2020. Gamblers aged 29–60 years who self-reported that they had experienced gambling-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Participants in the workshop expressed the wish that this should be an independent organisation. This echoes the findings of a recent UK qualitative study (Nyemcsok et al. , 2021) involving 20 experts by experience engaged in informing strategies to prevent or reduce gambling harm.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Participants in the workshop expressed the wish that this should be an independent organisation. This echoes the findings of a recent UK qualitative study (Nyemcsok et al. , 2021) involving 20 experts by experience engaged in informing strategies to prevent or reduce gambling harm.…”
Section: Discussionsupporting
confidence: 81%
“…, 2021) involving 20 experts by experience engaged in informing strategies to prevent or reduce gambling harm. Here their participants concluded that experts by experience should be seen as valuable stakeholders in co-producing support strategies to reduce gambling harms and also recommended new independent structures as a potential mechanism for representing people affected by gambling related harms (Nyemcsok et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant qualitative research has primarily focused on the perspectives of professional key informants, 18,19 young people and their parents 20 and people who have specifically experienced gambling problems or harm. 21,22 Understanding the perspectives of different population subgroups that engage in gambling is critical in informing the design of transformative public health and health promotion strategies.…”
Section: Women's Perceptions Of Strategies To Address the Normalisati...mentioning
confidence: 99%
“…The findings from this study demonstrate that young people are capable of discussing strategies that could reduce the normalisation of gambling and prevent gambling related harm. It is important to recognise that strategies recommended by young people in this study are similar to de-normalisation and harm prevention strategies that have been endorsed by public health experts, key stakeholders, and those with lived experience of gambling harm [47][48][49]. For example, there is clear support within the public health community for reducing the accessibility and availability of gambling products in communities, specifically a reduction of EGM licences and gambling venue opening hours [31,48].…”
Section: Discussionmentioning
confidence: 88%